1995
DOI: 10.1159/000288956
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Somatic Causal Attributions in Primary Care Patients with Fatigue

Abstract: Researchers in the field of chronic fatigue in tertiary care found that patients’ somatic (e.g. viral) explanations for their condition may lead to chronicity of symptoms. We studied the influence of a somatic attributional bias on outcome and reported symptoms in primary care patients with fatigue. We compared fatigue scores on a specific scale, and number of presented symptoms, in two groups of primary care patients with ‘functional’ fatigue: 75 with a high score on the somatic subscale of the Fatigue Attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In this study, the alexithymie trait is not a categorical concept connected only to certain nosographie structures, but is a dimensional factor having an etiopathogenetic role in somatization [2][3][4], Alexithymia is the result of the interaction between the neurovegetative component (exasperation of sympathetic reactivity) [12,13] and the cognitive component (deficit in the cognitive processing of emotions experienced somatically) [3,4,10,11]. Therefore, the theoretic and psychometric applica tions of the alexithymie concept to the field of somatiza tion represents a reliable operative instrument for the detection of these pathologies [40][41][42][43][44], Nevertheless, its application to a specific nosographie area (e.g. somato form disorders) cannot provide a complete explanation for the etiopathogenesis of these syndromes.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the alexithymie trait is not a categorical concept connected only to certain nosographie structures, but is a dimensional factor having an etiopathogenetic role in somatization [2][3][4], Alexithymia is the result of the interaction between the neurovegetative component (exasperation of sympathetic reactivity) [12,13] and the cognitive component (deficit in the cognitive processing of emotions experienced somatically) [3,4,10,11]. Therefore, the theoretic and psychometric applica tions of the alexithymie concept to the field of somatiza tion represents a reliable operative instrument for the detection of these pathologies [40][41][42][43][44], Nevertheless, its application to a specific nosographie area (e.g. somato form disorders) cannot provide a complete explanation for the etiopathogenesis of these syndromes.…”
Section: Resultsmentioning
confidence: 99%
“…These beliefs have been correlated with poor prognosis [20], increased symptoms [21] and a greater loss of functional ability [22]. It has also been suggested that this attribution style might be a vulnerability factor in developing CFS/ME [15].…”
Section: Introductionmentioning
confidence: 99%
“…There was no consistent relationship between expectations and health related locus of control in a trial of acupuncture, 8 and no correlation between locus of control and PROs in a randomized treatment trial for fatigue in primary care patients. 9 …”
Section: Discussionmentioning
confidence: 99%